RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6. (December 2019) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: Methyl 2-octynoate was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that methyl 2-octynoate is not genotoxic. Data provided methyl 2-octynoate a NESIL of 110 μg/cm 2 for the skin sensitization endpoint. The repeated dose, developmental and reproductive, and local respiratory toxicity endpoints were evaluated using the TTC for a Cramer Class II material, and the exposure to methyl 2-octynoate is below the TTC (0.009 mg/kg/day, 0.009 mg/kg/day, and 0.47 mg/day, respectively). The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; methyl 2-octynoate is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; methyl 2-octynoate was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: Methyl 2-octynoate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.